AFTERWORD: ONE PERSON’S TERRORIST IS ANOTHER PERSON’S FREEDOM FIGHTER, ONE PERSON’S JIHAD IS ANOTHER’S CRUSADE: REFLECTIONS ON THE TOKYO REELS FILM FESTIVAL BY SUBVERSIVE FILM AT THE DOCUMENTA 15, 2022 - Shaw, Wendy M. K (Disentangling Jihad, Political Violence and Media, 2023)
Near the end of my one long (very long) day in early September spent Nexploring the venues that staged the fifteenth edition of the quintennial exhibition Documenta held in the city of Kassel, I came through a narrow dark hallway in the former industrial park of the Hübner Company (a venue called the Hübner Areal), where mass transportation vehicles had, until recently, been manufactured. The black back of a film screen initially blocked my view of the cavernous dark space, soon to reveal on its other side a rise of black bleacher-style seating from which to watch the films projected